SOCIAL-ECOLOGICAL SYSTEM OF SEAGRASS AND SMALL-SCALE FISHERIES CONNECTIVITY IN MALANG RAPAT AND BERAKIT VILLAGES, BINTAN DISTRICT, RIAU ISLANDS - Muhammad Nur Arkham; Luky Adrianto; Yusli Wardiatno (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2015)
Seagrass ecosystem has important roles in ecological and social factors to support fisherman income. The purpose of this research was to map the social-ecological system connectivity of seagrass with small-scale fisheries with networks perspective, to identify social-ecological connectivity of seagrass with fisheries resource availability approaches in small-scale fisheries, and to estimate the benefits of fish resources relation to seagrass ecosystem in Malang Rapat and Berakit vilages. Social-ecological system connectivity of seagrass was proven by the spatial distribution of fishing areas, networks map markets, and dynamics of small-scale fisheries catches in the study site. Social-ecocoligal connectivity of seagrass was also proven by fish catches dominated by Siganidae, Scaridae, Lethrinidae, and Lutjanidae families. The fishermen income was supported by seagrass ecosystem connectivity which contributed revenue from fish catches totally Rp 202,124,00/day in Malang Rapat village and Rp. 193,151,00/day  in Berakit village. Other benefit of seagrass ecosystem located nearby the beach was that the fishermen can have an easy access or less fuel for fishing operation.Keywords: seagrass ecosystem, network map, connectivity, small-scale fisheries, social-ecological system, Riau islands